How do plants maintain pH and ion homeostasis under saline-alkali stress? - Li, Jing; Yang, Yongqing (Frontiers in Plant Science, 2023)
Salt and alkaline stresses often occur together, severely threatening plant growth and crop yields. Salt stress induces osmotic stress, ionic stress, and secondary stresses, such as oxidative stress. Plants under saline-alkali stress must develop suitable mechanisms for adapting to the combined stress. Sustained plant growth requires maintenance of ion and pH homeostasis. In this review, we focus on the mechanisms of ion and pH homeostasis in plant cells under saline-alkali stress, including regulation of ion sensing, ion uptake, ion exclusion, ion sequestration, and ion redistribution among organs by long-distance transport. We also discuss outstanding questions in this field.